Broadening the Horizon of International Student Mobility Programme: Transformation of the EduTour Programme to Beyond Normal - Soubakeavathi, Rethinasamy; Tatsuhiro, Ohkubo (2021)
The intense advancement in globalization in the past two decades has prompted the need for internationalization of higher education. Institutions of higher learning have realigned their approaches to include initiatives to develop their graduates’ global mindedness that would underpin their personal and professional lives. One of the strategies employed to meet this goal is through student mobility programmes which require experiences with host universities ranging from a few days to a year in length. This paper provides an illustration of the international student mobility programme called EduTour which is collaboratively designed by Universiti Malaysia Sarawak (UNIMAS) and Utsunomiya University Japan (UU), describes its journey from face-to-face to virtual, to the creation of intellectual property (IP) and commercialisation. In 2017, UNIMAS and UU signed the Memorandum of Understanding to strengthen their collaboration in teaching, learning and research. One of the initiatives is to establish student mobility programmes. After several rounds of discussion between UNIMAS and UU academics, the EduTour which is a two-week programme hosted by UNIMAS was planned and successfully implemented in 2018. Following its huge success, the programme continued in 2019 and 2020 with an increased number of participants and improvements made based on the feedback gathered from the participants. The EduTour includes English language classes based on Sustainable Development Goals (SDG) themes, campus tour, faculty visits, visits to historical sites and highlights of Kuching, recreational activities, food and cultural exchanges. Throughout the programme, UNIMAS participants take on the role of student buddies and provide a holistic support system that adds a special meaning to the programme. They are actively involved from welcoming the UU students and staff at the airport, as teaching assistants during the English classes, local guides during the visits, playmates during recreational activities, co-performers during the closing event, right up to bidding adieu at the airport. While the EduTour participants’ friendship continues beyond the programme through various social media platforms, it also became a catalyst for the students’ participation in other exchange programmes, internships, and scholarship opportunities. However, the EduTour’s continuity in 2021 was blurred by the travel restrictions imposed due to the COVID-19 pandemic. Nevertheless, motivated by requests from previous and potential participants and the valuable experiences gained from successfully carrying out the programme for three consecutive years, UNIMAS and UU decided to continue offering the programme despite all odds. UNIMAS and the UU coordinators discussed the possibility of conducting the EduTour virtually without compromising its quality. Decision was made to employ the hybrid approach with a combination of pre-recorded contents and live interactions that are similar to the old normal EduTour programme. The new beyond normal programme was aptly named e-EduTour and successfully carried out in February 2021. The uniqueness of the e-EduTour unfolded the opportunity for the creation of IP followed by the commercialisation of the programme. The presentation will discuss the full cycle of the student mobility programme from the improvements made based on the feedback gathered, to the application for IP and commercialisation of the beyond normal e-EduTour Module.